Advanced Polymer Nanocomposites (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue, entitled “Advanced Polymer Nanocomposites”, collects high-level original and review papers, focused on scientific discussions and practical applications in the field of functional polymer nanocomposites, including (a) optoelectronic materials (papers 1–6), (b) biomedical materials (papers 7–12), and (c) other functional polymer nanocomposites (papers 13–18).